A pintura de quadratura landiana em Belém do Pará - DINIZ, Virgínia Lúcia Guerreiro (Universidade Federal do Pará, 2014)
In the second half of the eighteenth century, the city of Belém went through a great economic expansion, which reflected positively in its architecture, with the erection of impressive religious temples in the current historical center, such as São João Batista Church. This work examined the quadrature painting performed by the architect Antônio Landi in São João Batista Church’s interior, in Belém, to identify the paint used in that rare painting, based on the artist’s claim that he used the pigment extracted from Arrabidaea chica (H & B) Verlot, popularly known as carajiru, and the changing process this pigment went through. Therefore, it was possible to get important data for its preservation and restoration. The study was divided into three stages: first, there was a historical research focused on literary works about paints, pigments and dyes used in religious architecture during the Amazonian colonial period; on the influence of the religious orders on the decoration of the temples; on Landi’s educational background and his works in Belém; and on the technique called quadrature painting. During this stage, the damage in the painting was mapped out and the color patterns were assessed through colorimetry, and the temperature of the painted walls was measured with an infrared camera. The second stage consisted of a laboratory analysis of the paint used by Landi and the pigment extracted from carajiru through optical microscopy, scanning electron microscopy, X-ray diffractometer and infrared spectrometer. The data surveyed allowed the identification and comparison of the materials used in quadrature painting. Finally an experiment with the paint produced from the pigment extracted from carajiru. The historical research contributed to the comprehension of the properties of the paint, pigments and dyes. The interdisciplinary study enabled the conduct of technological procedures, and allowed the development of diagnoses that are helpful to establish preventive conservation measures and proposals for future restoration interventions.